Prevalence of hepatitis E infection in the general population of Iran: a systematic review and meta-analysis. (April 2017) - Hadifar, Shima; Sedighi, Mansour; Mostafaei, Shayan; Miri, Ali; Amiri, Hamed; Abiri, Ramin; Babaei, Farhad; Kabir, Kourosh; Moghoofei, Mohsen
Aim: Hepatitis E is a form of acute viral hepatitis, which is caused by hepatitis E virus (HEV). The study objective was to evaluate the prevalence of HEV to provide an overall relative frequency in Iran.Methods: In this study, databases such as PubMed and Scopus were searched using the following keywords according to MeSH, "Hepatitis E virus", "Epidemiology", "Enzyme-linked immunosorbent assay (ELISA)" and "Iran". Then studies which had reported prevalence of HEV were selected.Results: We selected 36 researches out of 9246 for our study. From all the samples, the pooled estimated prevalence of HEV positive was 9.7%. It should be noted that HEV infection's relative frequency varied from 1.1% in Tehran to 46.1% in Ahvaz.Conclusion: HEV is common in Iran, although comparing to some neighboring countries, its prevalence is lower.